Response of the Antarctic Ionosphere to Some Intense Geomagnetic Storms - Mansilla, Gustavo Adolfo (2017)
The effect of geomagnetic storms on the mid-high latitude F2 region is studied. For that, foF2 data from four Antarctic stations were analyzed during three intense magnetic storms occurred in high solar activity (years 2002 and 2003). In general, negative storm effects irrespective of the local time were observed during the first part of the storms (main phase). Negative effects were also observed more often than positive effects during the first part of the recovery phase, which seems to indicate almost no longitudinal dependence in this stage of the storm. The negative effects frequently changed to positive during the last stage of the recovery. Several physical mechanisms were operative during the different stages of the storms.